Cinnamon teal breeding ecology in the San Luis Valley of Colorado - Setash, Casey M., author; Kendall, William L., advisor; Doherty, Paul F., Jr., committee member; Aldridge, Cameron L., committee member; Olson, David, committee member (Colorado State University. Libraries, 2018)
The foundation of effective waterfowl management is an abundant and resilient waterfowl population, which begins with an understanding of what drives population size and growth. Population growth rate is the product of a number of vital rates, all of which remain relatively unknown for the cinnamon teal (Spatula cyanoptera). I investigated the interactions between biotic and abiotic factors influencing the basic demographic rates of cinnamon teal during the breeding season in the San Luis Valley of Colorado. Specifically, I assessed the relationship between the habitat around a selected nest site and cinnamon teal nesting success. Additionally, I evaluated whether a relatively novel approach to surveying social groupings of waterfowl can act as an effective index of breeding effort and success for cinnamon teal, the intraspecific variation in nest attendance patterns during incubation and how it affects nest survival, and the rates at which breeding females and ducklings survive the breeding season. This research has the potential to enhance the understanding of the basic population ecology of this overlooked species and provide information about vital rates that can be used in future analyses and management of the population on a larger scale. I found that cinnamon teal select nest sites with habitat characteristics that are also associated with a higher probability of nest survival (Chapter 2, this thesis). Specifically, I observed cinnamon teal selecting nest sites characterized by a lower proportion of forbs relative to what was available, which were also associated with higher nest survival among the nests I observed. I established that weekly transect surveys assessing the social groupings of cinnamon teal throughout the breeding season have the potential to act as an index of reproductive success if done on a larger scale (both temporally and geographically; Chapter 3, this thesis). I also found differences in the nest attendance patterns during early incubation compared to late incubation, which were also impacted by time of day and temperature (Chapter 4, this thesis). Finally, I estimated breeding season duckling and hen survival rates that were comparable to other waterfowl species and provided suggestions for future cinnamon teal researchers (Chapter 5, this thesis).